2011
DOI: 10.1021/ja205369h
|View full text |Cite
|
Sign up to set email alerts
|

Striking Stability of a Substituted Silicon(II) Bis(trimethylsilyl)amide and the Facile Si–Me Bond Cleavage without a Transition Metal Catalyst

Abstract: Silicon(II) bis(trimethylsilyl)amide (LSiN(SiMe(3))(2), L= PhC(NtBu)(2)) (2) has been synthesized by the reaction of LSiHCl(2) with KN(SiMe(3))(2) in 1:2 molar ratio in high yield where 1 equiv of the latter functions as a dehydrochlorinating agent. 2 exhibits a high stability up to 154 °C and can be handled in open air for a short period of time without any appreciable decomposition. An amazing five-membered cyclic silene (3) results from the cleavage of one Si-Me bond of 2 with an adamantyl phosphaalkyne. 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 87 publications
1
68
0
2
Order By: Relevance
“…Activation of white phosphorus by silylene amide 75 proceeds differently to the analogous reaction of 71 , affording acyclic P 4 ‐heterotriene 32 (Scheme ) …”
Section: Structure and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of white phosphorus by silylene amide 75 proceeds differently to the analogous reaction of 71 , affording acyclic P 4 ‐heterotriene 32 (Scheme ) …”
Section: Structure and Synthesismentioning
confidence: 99%
“…[63] The group of Scheer reported that the reaction of chlorosilylene 71 with zirconium complex 74 leads to am ixture of sixand four-membered Si,P-heterocycles 38 and 35 (Scheme15), which were isolated in low yields (14 %a nd 17 %, respectively). [64] Activation of white phosphorus by silylene amide 75 [89] proceeds differently to the analogous reaction of 71,a ffording acyclic P 4 -heterotriene 32 (Scheme 16). [60] Reduction of a1 :1 mixture of chlorosilylene 71 and TipPCl 2 with KC 8 gave 1,4-diphospha-2,3-disilabutadiene 33,w hile the reduction of a1 :2 mixture with excess KC 8 afforded the corresponding1 ,3-diphospha-2-silaallyl potassium 34 (Scheme17).…”
Section: Synthesesb Ased On Reactivity Of Stable Silylenecomplexesmentioning
confidence: 99%
“…Bringt man das Bis(trimetylsilyl)‐substituierte N‐heterocyclische Silylen (53) mit dem Phosphaalkin AdaCP zur Reaktion, so wandert eine Methylgruppe aus der Trimethylsilyl‐ Einheit an den Phosphor des Phosphaalkins. Letztlich ist dies also nicht nur eine Addition an die CP‐Dreifachbindung sondern auch die Aktivierung einer Si‐Me‐Bindung (57) 1_76. Das ebenfalls durch Stickstoffdonorgruppen stabilisierte SnI‐Dimer (58) reagiert mit Schwefel und Selen und bildet dabei im Fall des Selens eine den Carbonsäureanhydriden homologe Verbindung des Typs ArSn(=Se)SeSn(=Se)Ar (59) 1_77,1_78…”
Section: Highlights Aus Der Chemie Der Elemente Der Gruppe 14unclassified
“…The reaction of the amidinate-stabilized silicon(II) amide [LSiN(SiMe 3 ) 2 ] (1) [15] with GeCl 2 ·dioxane in toluene afforded the silicon(II)-germanium(II) adduct [L{(Me 3 Si) 2 N}Si! GeCl 2 ] (2; Scheme 2), which was isolated as an air-and moisture-sensitive colorless crystalline solid in high yield (73 %).…”
mentioning
confidence: 99%